2004
DOI: 10.1525/aa.2004.106.1.17
|View full text |Cite
|
Sign up to set email alerts
|

Human Behavioral Organization in the Middle Paleolithic: Were Neanderthals Different?

Abstract: Interwoven with the debate regarding the biologic replacement of Neanderthals by modern humans is the question of the degree to which Neanderthals and modern foragers differed behaviorally. We consider this question through a detailed spatial analysis of artifacts and related evidence from stratified living floors within a 49–69 k.y.a. rock shelter site, Tor Faraj, in southern Jordan. The study involves a critical evaluation of living floors, the identification of site structure, and the decoding of the site s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
48
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(52 citation statements)
references
References 33 publications
2
48
0
2
Order By: Relevance
“…Macrobotanical analysis at the Middle Palaeolithic site of Kebara (Israel) identified the charred remains of seeds preserved in hearths and found evidence for use of legumes, acorns and pistachio nuts (Lev et al, 2005). Studies of plant microremains preserved in soils (Henry et al, 1996(Henry et al, , 2004Albert et al, 1999Albert et al, , 2000Rosen, 2003) and dental calculus (Henry et al, 2011) from Near Eastern sites suggest that Neanderthals may have consumed a variety of plant foods such as date palms and grains. In cold northern European environments, the study of phytoliths and starch grains in dental calculus from Spy Cave (Belgium) indicated that grass seeds and underground storage organisms were part of Neanderthal diet (Henry et al, 2011).…”
Section: Evidence Of Neanderthal Plant Consumptionmentioning
confidence: 99%
“…Macrobotanical analysis at the Middle Palaeolithic site of Kebara (Israel) identified the charred remains of seeds preserved in hearths and found evidence for use of legumes, acorns and pistachio nuts (Lev et al, 2005). Studies of plant microremains preserved in soils (Henry et al, 1996(Henry et al, , 2004Albert et al, 1999Albert et al, , 2000Rosen, 2003) and dental calculus (Henry et al, 2011) from Near Eastern sites suggest that Neanderthals may have consumed a variety of plant foods such as date palms and grains. In cold northern European environments, the study of phytoliths and starch grains in dental calculus from Spy Cave (Belgium) indicated that grass seeds and underground storage organisms were part of Neanderthal diet (Henry et al, 2011).…”
Section: Evidence Of Neanderthal Plant Consumptionmentioning
confidence: 99%
“…Charred seeds have been found in the Mousterian levels of Kebara (Lev et al, 2005) and Gorham's Cave (Barton et al, 1999). Phytoliths from edible plants have been recovered from sediments in several Near Eastern Neanderthal sites (Henry et al, 1996(Henry et al, , 2004Albert et al, 1999Albert et al, , 2000Rosen, 2003). More direct evidence for Neanderthal use of plants comes from studies of residues on stone tools from several sites in France (Hardy and Moncel, 2011;Hardy et al, 2013), and from the study of residues in dental calculus from El Sidron, Spain (Hardy et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Middle Paleolithic | symbolism | art | Iberia | cognition C onsiderable debate surrounds the Neanderthals' cognitive abilities (1)(2)(3)(4)(5)(6)(7), and the view that the Neanderthals did not have the same cognitive capacities as modern humans persists in the literature (8) despite evidence to the contrary (9)(10)(11)(12)(13)(14)(15). One of the arguments against Neanderthals' modern cognition is their apparent inability to generate cave art (16)(17)(18)(19).…”
mentioning
confidence: 99%